Case report: Clinical success targeting BRAF-mutated, hormone receptor positive, HER2- negative advanced breast cancer patient with BRAF-inhibitor plus MEK- inhibitor - López de Sá, Alfonso; de Luna, Alicia; Antoñanzas, Mónica; García-Barberán, Vanesa; Moreno-Anton, Fernando; García-Sáenz, Jose A. (Frontiers in Oncology, 2022)
Background: Hormone receptor-positive, human epidermal growth factor 2-negative advanced breast cancer patients have had a wide range of therapeutical options since the incorporation of targeted therapies alongside classic chemotherapy. However, because of their disease, virtually all patients will eventually experience disease progression that might compromise their lives. Thriving investigation regarding molecular therapies has provided clinicians with new options for the treatment of many cancer patients. Dabrafenib and trametinib combination has proven useful in treating malignant melanoma patients harboring a BRAF V600E mutation, improving progression-free survival and overall survival, and it has been tested in other tumors. Here we report the case of a metastatic breast cancer patient harboring a BRAF V600E mutation that achieved complete response with dabrafenib and trametinib combination.